The Icelandic Lutheran Synod of America and its missionary in Japan, 1916–1941: Steingrímur Octavius Thorlakson - Ingvarsdóttir, Kristín (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2022)
In 1910, despite low membership and limited funds, the Icelandic Lutheran Synod of America began directly supporting mission work in Asia. It first sponsored a Danish missionary who was serving in India and later commissioned one of its own members, Steingrímur Octavius Thorlakson (1890–1977), to carry out missionary work in Japan, where he ended up serving for 25 years, from 1916 to 1941. Although the synod’s Asia initiative was well known within the Icelandic community, as was Octavius himself during his lifetime, the venture has not become a substantial chapter of the history of Icelanders in North America. The aim of this article is twofold: first, to shed light on the background and nature of the Icelandic Synod’s missionary enterprise in Asia, and second, to examine the initiative and Octavius’ career from the perspective of mobility and international influences in the early 20th century.